Buschke Scleredema, case report - R. De Pasquale; P. Gangemi; C. Leonetti; M. Di Gangi; G. Fichera; R. Leonardi; R. Foti (PAGEPress Publications, 2011)
Buschke Scleredema is a rare connective tissue disorder of unknown aetiology, characterized by thickening of the dermis whose characteristics may mainly to mime systemic sclerosis, eosinophilic fasciitis and cutaneous amyloidosis. Scleredema may be associated with a history of an antecedent febrile illness, diabetes mellitus, or blood dyscrasia. Scleredema can be classified into three clinical groups; each has a different history, course, and prognosis. Each one of these share reduction in chest articular movements and limitation of limbs movements. The skin histology is characterised by thickened dermis and increased spaces between large collagen bundles due to increased deposition of mucopolysaccharide in the dermis. Differential diagnosis can be made considering the typical clinical features and the histologic peculiarity. No therapy has been found effective. The autors describe a case of Buschke Scleredema successfully treated by steroids and colchicines. Clinical evaluation of skin induration and thickness as well as ultrasonography were performed at baseline and after treatment.